Органічне землеробство як основа збалансованого природокористування та сталого розвитку - Сябро, Д. О.; Босюк, Альона Сергіївна (ГО "Міжнародна наукова гільдія", 2026)
The report is devoted to the role of organic farming as a key mechanism for implementing the principles of sustainable development and balanced environmental management in Ukraine. The main threats of traditional intensive farming (pollution, land degradation) and the advantages of the organic approach, which contributes to the restoration of soil fertility, the preservation of biodiversity and the achievement of a neutral level of land degradation, are considered. Successful real cases of organic production in Ukraine are analyzed.
Keywords: сталий розвиток; землеробство; природокористування; збалансоване природокористування; природні ресурси; екологія